Case report: The safety of laparoscopic surgery for the retroperitoneal bronchogenic cyst - Li, Hancong; Xu, Jun; Feng, Qingbo; Cai, Zhaolun; Li, Jiaxin (Frontiers in Oncology, 2022)
Introduction Bronchogenic cyst is a congenital aberration of bronchopulmonary malformation with bronchial-type, pseudostratified cylindrical epithelium. They are usually discovered in the mediastinum and intrapulmonary but are rarely encountered in retroperitoneum. We report a case of the retroperitoneal bronchogenic cyst and perform a literature review to summarize the safety of laparoscopic resection for this rare disease. Case presentation We report a 57-year-old woman who was admitted to our hospital with no clinical symptoms and was found by chance to have masses in the adrenal gland area during a routine physical examination. An abdominal CT examination revealed a cystic lesion was found in the left suprarenal region. Afterward, the patient underwent a laparoscopic exploration. Histopathological findings confirmed the diagnosis of a retroperitoneal bronchogenic cyst. The patient recovered uneventfully without signs of recurrence during a 1-year follow-up period. Conclusion Bronchogenic cyst is rare in the retroperitoneal region. It should be considered as one of the differential diagnoses of a retroperitoneal neoplasm, especially in the left retroperitoneal region. Laparoscopic surgery is technically feasible and safe for the treatment of patients with a retroperitoneal bronchogenic cyst.